Tax culture and compliance with tax obligations - ORDOÑEZ VASQUEZ, Marianela (2020)
The purpose of this study is to determine the relationship of the tax culture and the tax obligations of the merchants of the Las Pirias district, applied research at the descriptive level, of a non-experimental cross-sectional design, since information was collected in only a period of time without manipulating variable Some, describing the events as they occurred using theories that gave the necessary support, the sample is made up of 80 merchants who carried out their activities in the mentioned district. To collect the data, the technique used was the survey, and a questionnaire with 20 items. It was obtained as a result that the tax culture is related in a positive way to the fulfillment of tax obligations, since by applying the survey it was determined that both variables are at a medium level, therefore they are directly related, In other words, if the tax culture is improved, the level of compliance with tax obligations will be higher.Keywords: culture, compliance, obligations, taxation, tax knowledge.